To solve for y, we need to isolate y on one side of the equation.
Ax + By = C
Subtract Ax from both sides:
By = -Ax + C
Divide both sides by B:
y = (-A/B)x + (C/B)
Therefore, the equation solved for y is y = (-A/B)x + (C/B).
The equation of a line is given by Ax + By = C. Solve for y.
3 answers
that wasn't an option,here are the options:
A. y=C-(Ax/B)
B. y=C-Ax
C. y=B(C-Ax)
D. y=(C/B)-(Ax/B)
A. y=C-(Ax/B)
B. y=C-Ax
C. y=B(C-Ax)
D. y=(C/B)-(Ax/B)
To solve for y in the equation Ax + By = C, we need to isolate y.
Ax + By = C
Subtract Ax from both sides:
By = -Ax + C
Divide both sides by B:
y = (-Ax + C)/B
Rearranging the terms:
y = (-A/B)x + C/B
Comparing the equation with the given options, we can see that the correct answer is option D: y = (C/B) - (Ax/B).
Ax + By = C
Subtract Ax from both sides:
By = -Ax + C
Divide both sides by B:
y = (-Ax + C)/B
Rearranging the terms:
y = (-A/B)x + C/B
Comparing the equation with the given options, we can see that the correct answer is option D: y = (C/B) - (Ax/B).